Faktor-Faktor Yang Mempengaruhi Produksi Jagung Di Kecamatan Poigar Kabupaten Bolaang Mongondow - Tangkowit, Christina Deisy; Manginsela, Elsje Pauline; Lumingkewas, Jelly Ribka (Sam Ratulangi University, 2023)
This study aims to determine what factors affect maize production in Poigar District. This research was conducted in Poigar District where most of the people are farmers. This research activity was carried out from May to June in 2022. The results showed that the results of hypothesis testing in the F (simultaneous) test showed that together the variable land area, seed variable, urea fertilizer variable, phonska fertilizer variable, labor variable work, pesticide variables, and farming experience variables affect the amount of corn production in Poigar District. And testing the hypothesis on the T test that partially the factors that affect corn production at = 0.05 are factors that significantly affect corn production in Poigar District, namely factor (X1) land area, factor (X4) Phonska fertilizer, factor (X5) significant workforce in Poigar District.